Application of the Poedji Rochjati Score on Knowledge and Attitudes of Cadres in Early Detection of High Risk Pregnancy in the Working Area of the Penyengat Olak Health Center, Jambi District, Outer City, Jambi Regency: Penerapan Skor Poedji Rochjati Terhadap Pengetahuan dan Sikap Kader pada Deteksi Dini Kehamilan Risiko Tinggi di Wilayah Kerja Puskesmas Penyengat Olak Kecamatan Jambi Luar Kota Kabupaten Jambi - Nopiska Lilis, Dewi; Murdayah (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to apply the Poedji Rochjati Score in increasing cadres' knowledge and attitudes regarding early detection of high-risk pregnancies at Penyengat Olak Health Center, Jambi Luar Kota District, Jambi Regency. The activities took place in July and August, including training at the Community Health Center and a visit to Bird's Nest Bali Village. The pre-test results show that cadres have low knowledge, with the lowest score being 3 and the highest being 7 out of 10 questions. After the intervention, the post-test score increased significantly, with the lowest score being 8 and the highest being 10. These findings indicate that the application of the Poedji Rochjati Score is effective in increasing the knowledge and attitudes of cadres, thereby strengthening efforts to detect early high-risk pregnancies in the area. In conclusion, the use of the Poedji Rochjati Score contributes positively to cadres' understanding of detecting high-risk pregnancies.